2008
DOI: 10.1038/hdy.2008.67
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genomics of Atlantic salmon: SNPs associated with QTLs for adaptive traits in parr from four trans-Atlantic backcrosses

Abstract: European Atlantic salmon (Salmo salar) differ in skin pigmentation and shape from the North American lineage of Atlantic salmon but the genetic basis of these differences are poorly understood. We created four large (N ¼ 300) backcross families by crossing F1 hybrid male siblings to two females from the European and two from the North American aquacultural strains. We recorded 15 morphological landmarks and two skin pigmentation, three growth and three condition traits on parr. The backcross families were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 47 publications
(60 reference statements)
4
88
0
Order By: Relevance
“…(b) F CT . (c) QTL (with number showing chromosome and the letter the study “a” Baranski et al., 2010; “b” Boulding et al., 2008; “c” Gutierrez et al., 2012 males time 3, “d” QTL s from Gutierrez et al., 2012 females time 3. “e” Gutierrez et al., 2012 females time 4, “f” Gutierrez et al., 2012 Males time 4, “g” Houston et al., 2009; “h” Petersen et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) F CT . (c) QTL (with number showing chromosome and the letter the study “a” Baranski et al., 2010; “b” Boulding et al., 2008; “c” Gutierrez et al., 2012 males time 3, “d” QTL s from Gutierrez et al., 2012 females time 3. “e” Gutierrez et al., 2012 females time 4, “f” Gutierrez et al., 2012 Males time 4, “g” Houston et al., 2009; “h” Petersen et al.…”
Section: Resultsmentioning
confidence: 99%
“…eF1 hybrids (2001) and F1 backcrosses (2005) between NA and EU (Mowi) subspecies of Salmo salar (Boulding et al., 2008). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, a QTL for both BW and K detected on Atlantic salmon linkage group AS-8qa (markers Ssa401UoS, BHMS313A) appears to share homology to the short arm of rainbow trout linkage group RT-23 (i.e., RT-23p)[41]. Similarly, BW and K QTL have been localized to the duplicated homeologous linkage groups AS-22/24 [43]. These homeologs in Atlantic salmon share homology to the duplicated homeologs RT-7/15 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Gilbey (2003) reported the markers Ssa14, Ssa48, and μ20.19 to be significantly associated with QTL affecting fish size during development from parr to smolt in backcrosses between Scottish and Canadian Atlantic salmon. Additionally, Boulding et al (2008) found SNP markers on linkage groups AS9, AS18, and AS22 (derived from ASalBASE; http://www. asalbase.org) to be associated with weight and condition factor and markers on AS10 and AS12 to be linked to morphometric variables in trans-Atlantic crosses of Atlantic salmon.…”
Section: Discussionmentioning
confidence: 99%